The next generation of research in interpreter education : pursuing evidence-based practices - Roy, Cynthia B., 1950-; Winston, Elizabeth A. (Interpreter education series., 2018)
"Volume builds on two traditions in education and research - long standing traditions in general and traditions that have taken root and continue to spread through our field of interpreter preparation"--